UNPACKING VALUE: HOW BUSINESS STRATEGY, OWNERSHIP, AND PERFORMANCE SHAPE STOCK PRICES OF LQ45 MANUFACTURING FIRMS (2019–2023) - Junianto, Prima Ayu Novita; Agung Gde Satia Utama , Anak (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the interplay between business strategy, corporate performance, and managerial ownership in shaping the stock prices of LQ45listed manufacturing firms in Indonesia from 2019 to 2023. Despite analogous financial metrics, it addresses persistent valuation asymmetries between StateOwned Enterprises (SOEs) and nonSOEs. An integrativecomparative analytical framework is developed, positioning ownership structure as a moderating variable within the dynamics of an emerging market. Employing a quantitative methodology, the study applies panel data regression to test directional causality across key indicators, including Asset Utilisation Efficiency (AUE), Return on Equity (ROE), Return on Assets (ROA), Earnings per Share (EPS), and the proportion of managerial ownership. The empirical workflow comprises five sequential stages: (1) computation of financial ratios, (2) strategic categorisation via quintile scoring, (3) regressionbased model estimation, (4) diagnostic testing for normality (Kolmogorov–Smirnov) and heteroskedasticity, and (5) comparative testing moderated by ownership classification. Findings reveal AUE as a statistically significant determinant of stock price behaviour, while corporate performance and managerial ownership exhibit relatively weaker isolated effects. The study offers strategic insights for capital market actors and public sector stakeholders navigating valuation complexities in the postpandemic era.